Flight fare prediction using machine learning - Noyon, Md. Shaim Hosan; Islam, Tanzidul; Islam, Solaiman; Reejon, Md. Refayet Islam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.